The Effect of Corporate Governance, Funding Decisions and Working Capital Turnover on Firm Value - Rifqi Ali Fadillah; Ibram Pinondang Dalimunthe (Pusat P2M Politeknik Negeri Batam, 2025)
This study aims to examine the effect of corporate governance, funding decisions, and working capital turnover on firm value in the consumer non-cyclical sector listed on the Indonesia Stock Exchange (IDX) during the period 2019–2023. The population consists of 125 companies, from which 69 were selected as the final sample using purposive sampling. The data were analyzed using panel data regression in EViews 12. Firm value in this study is measured using the Price-to-Book Value (PBV) ratio. Corporate governance is assessed through the ASEAN Corporate Governance Scorecard (ACGS); funding decisions are proxied by the Debt-to-Asset Ratio (DAR); and working capital turnover is calculated as net sales divided by net working capital. The results show that, in part, only funding decisions have a significant effect on firm value, while corporate governance and working capital turnover do not. The model is statistically valid as shown by the F-test, but the coefficient of determination (R²) is relatively low, at 7.47%, indicating that the explanatory variables account for only a small portion of the variation in firm value.